PENGEMBANGAN SDM MELALUI KOMPENSASI, MOTIVASI DAN KEPUASAN KERJA TENAGA PENDIDIK DI SMK ISLAM KREMBUNG - Yaqin, Mohammad Nurul; Subiyantoro, Subiyantoro (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2024)
This study examines human resource development (HRD) through aspects of compensation, motivation, and job satisfaction among educators at SMK Islam Krembung. Using a qualitative approach with a case study method, the research was conducted through interviews and observations of the school principal and educators. The results show that fair and competitive compensation, including basic salary, allowances, and supporting facilities, plays an important role in improving the performance of educators. Motivation, both intrinsic and extrinsic, has proven effective in creating a conducive work environment and encouraging self-development of educators. High job satisfaction, characterized by a balance between workload and compensation as well as harmonious relationships among colleagues, contributes to increased commitment and loyalty of educators. The research concludes that good management of these three aspects can encourage optimal HR development, which ultimately contributes to improving the quality of education in schools. It is recommended that school management consistently pay attention to and manage aspects of compensation, motivation, and job satisfaction to support sustainable human resource development.